Turnament Tangram, Merangsang Minat Bermatematika Siswa SD Dan Alternatif Ice Breaking Oleh Guru - Destini, Rita; Putri, Elia; Afriyanti Nst, Lia; Pulungan, Khairunnisyah; Sari, Dwi Novita (LPPI UMN AL WASHLIYAH, 2023)
The learning that is currently carried out often uses monotonous learning methods so that the learning process is boring. In the era of industry 4.0, teachers are expected to carry out innovative learning using methods, interesting learning media tailored to learning objectives and teachers are also guided to be able to integrate learning with ICT, Culture so that students can understand the teaching material well and understand the usefulness of the material taught in daily life. Based on this, it is necessary for the PkM Team of Muslim Nusantara University to share knowledge about the learning model by using Tangram and Ice Breaking Tournaments to teachers at SD Negeri 106165 Marindal I, Patumbak District, Deli Serdang Regency. The result of the implementation of this PkM is that the teachers at SD Negeri 106165 Maridal I have understood and know how to use the Tangram and Ice breaking Tournament learning methods so that the learning implementation process is more interesting. Teachers at SD Negari 106165 Marindal I are very happy and enthusiastic in following the direction and guidance from the PkM Team of University Muslim Nusnatara Al-Washliyah.